A Healthcare Providers’ Survey for the Cognitive Rehabilitation of Multiple Sclerosis in France: From Research to Real Life - Hélène Brissart; Héloïse Joly; Clémentine Castro; Bruno Lenne (Sclerosis)
Introduction: Cognitive impairment (CI) is recognized as a very frequent feature of persons with multiple sclerosis (pwMSs). Multiple studies have demonstrated the effectiveness of cognitive rehabilitation (CR) in improving CI linked to cerebral functional connectivity facilitation and increased strategies to cope with daily living activities. Nevertheless, there is considerable heterogeneity in the methodologies and protocols proposed to pwMSs. Aim: This study aimed to establish a current state of CR for pwMSs, among different types of healthcare providers (HCPs) in France. Methods: A Web-based survey was conducted between March and September 2024 among HCPs involved in the care of pwMSs. Results: One hundred and one HCPs involved in the care of pwMSs participated in this survey. CR was considered efficient by 97% of HCPs, especially when multimodal. Based on the responses, CR is proposed mainly following cognitive complaints, for moderate or severe cognitive disorders, and at the onset of the disease (45%). HCPs mentioned several obstacles to the implementation of CR, notably the cost of remediation (37%), and the lack of availability of both professionals (58%) and patients (51%). Conclusions: This rehabilitation requires specific tools combined with psychoeducative advice provided by multidisciplinary HCPs.